(untitled) (Nonconventional Technologies Review, 2019)
The work is focused on the identification of specific elements that can have influence on specific generation of components for equipment used in unconventional technologies. In the first chapter are analyzed the specific processes that allow the generation of component by 3D printing thermoplastic solution type FDM or photo polymerization by DLP or SLA solution. They are determinate the similarities and differences between transfers of the energy for thermic plasticization and the transformation in solid structure from liquid material in the second part with CAM system. In the third part are analyzed the solutions to generated constructive components or assemblies by 3D processes CAM-CNC process. In the fourth part of the work was analyzed the specific 3D printing parts through this process of printing considered. In the last chapter it is determined the economic aspects of the parts generated by the 3D printed process used. The analysis will be done both by optical and dimensional measurement of the part in different points and by dimensional measurement of the part with digital measuring devices and optical method. The paper also refers to the methodology of generating of the part and the influence of the way they generated on the characteristics of the generated parts.